A Review of the Relationship Between Vitamin D and Parkinson Disease Symptoms - Fullard, Michelle E.; Duda, John E. (Frontiers in Neurology, 2020)
Vitamin D is a fat-soluble secosteroid that exerts its effects by binding to the vitamin D receptor (VDR), through which it directly and indirectly modulates the expression of hundreds to thousands of genes. While originally known for its role in regulating calcium homeostasis and metabolism, vitamin D is now associated with many other health conditions, including Parkinson’s disease (PD). A high prevalence of vitamin D deficiency has been noted in PD for at least the past two decades. These findings, along with the discovery that the VDR and 1α-hydroxylase, the enzyme that converts vitamin D to its active form, are highly expressed in the substantia nigra, led to the hypothesis that inadequate levels of circulating vitamin D may lead to dysfunction or cell death within the substantia nigra. Studies investigating the relationship between vitamin D status and PD, however, have been inconsistent. Two prospective studies examined the association between mid-life vitamin D levels and risk of PD and produced conflicting results – one demonstrated an increased risk for PD with lower mid-life vitamin D levels, and the other showed no association between vitamin D and PD risk. One of the most consistent findings in the literature is the inverse association between serum vitamin D level and motor symptom severity in cross-sectional studies. While these data suggest that vitamin D may modify the disease, another likely explanation is confounding due to limited mobility. Fall risk has been associated with vitamin D in PD, but more study is needed to determine if supplementation decreases falls, which has been demonstrated in the general population. The association between vitamin D and non-motor symptoms is less clear. There is some evidence that vitamin D is associated with verbal fluency and verbal memory in PD. Studies in PD have also shown associations between vitamin D status and mood, orthostatic hypotension and olfactory impairment in PD. While more research is needed, given the numerous potential benefits and limited risks, vitamin D level assessment in PD patients and supplementation for those with deficiency and insufficiency seems justified.